Implementasi Sequential Searching pada Pencarian Transaksi Bilyet Giro Wisma BCA Pondok Indah Berbasis Website - Bhakti Siswanto; Nia Nuraeni (Universitas Bina Sarana Informatika Kota Sukabumi, 2022)
Processing and archiving of power of attorney for depositing demand deposits at BCA Wisma BCA Pondok Indah still uses the manual method, namely storage in large folders based on grouping and alphabetically. With the large number of power of attorney stored at BCA Wisma BCA Pondok Indah, the process of providing teller transaction services is hampered in searching for the name of the customer who receives the checking account based on the account number, making it inefficient in terms of time and effort. The purpose of this study is to implement a sequential searching algorithm to facilitate the search for account numbers in the power of attorney archive system for depositing giro BCA Wisma BCA Pondok Indah. By using the waterfall method to overcome the above problems, in its development this system uses UML (Unified Modeling Language) object-oriented analysis methods such as Use Case Diagrams, Sequence diagrams, Activity Diagrams and Class Diagrams. Sequential Searching Algorithm can be implemented in the search for power of attorney archives based on account numbers. The programming language used in this application is PHP scripting and MySQL database and the system testing used is black box testing